Peran DKPP dalam Menjaga Profesionalitas Penyelenggara Pemilu: Penegakan Kode Etik Menurut UU 7 Tahun 2017 - Hafiz Sutrisno; Fakhry Firmanto (PT PUSTAKA CENDEKIA GROUP, 2024)
The enforcement of the code of ethics is a crucial instrument in maintaining the professionalism and integrity of election organizers. The Honorary Council of Election Organizers (DKPP) holds the mandate to uphold the code of ethics as regulated in Law Number 7 of 2017 concerning General Elections. This study aims to analyze the role of DKPP in maintaining the professionalism of election organizers through the enforcement of ethical codes. The research employs a normative juridical method with statutory and conceptual approaches. The results show that DKPP plays a strategic role in ensuring that election organizers, both the General Elections Commission (KPU) and the Election Supervisory Body (Bawaslu), perform their duties professionally, independently, and with integrity. DKPP enforces ethical codes through mechanisms of examination, ethical hearings, and the imposition of sanctions on violators. However, several obstacles exist in its implementation, such as limited authority to follow up on sanctions and overlapping perceptions between ethical and legal violations. In conclusion, DKPP’s role in enforcing the code of ethics is significant in maintaining the professionalism of election organizers, although institutional strengthening and regulatory harmonization are still needed to ensure more effective and fair ethical enforcement.